Effect of Thinning on the Tracheid Length in the Wood of Plantation-grown Cupressus lusitanica - Kaluba, W.; Ringo, W. N. (Indian Forester, 1985)
The effect of different thinning regimes on the tracheid length in the wood of 19 year old Cupressus lusitancia grown at Meru Forest project in Northern Tanzania was investigated. The thinnings were carried out at 5 year intervals beginning at 10 years of age. The results showed that the mean tracheld lengths of the wood obtained from plots that had been subjected to 20% and 33% thinning intensities did not differ significantly from the mean value in the wood obtained from the stands that had been subjected to 45% thinning intensity was significantly shorter than that of the wood from the unthinned stands.